Strategi Promosi Songket Palembang (Studi Kasus Kerajian Songket Cek Ipah) - Zainal Berlian (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2018)
The appeal of songket as a small and medium-sized industry or Small Business Menangah (UKM) is not only assessed by the market in terms of its quality and only its quality. More than that, the peculiarities of the Palembang region that are closely related to the history of the Palembang sultanate, which was famous for its glory, were able to provide more value in the marketing of Palembang songket.Unfortunately, this opportunity has not been maximized, so it is only natural that songket is not only able to run in place at the moment, with a minimal amount of production, with the reason to wait for foreign markets to pick up and maintain the local market. Even though the global market is wriggling and there are many outside markets for songket, it's time to be captured by songket craftsmen, either through increasing production, marketing strategies or improving quality in terms of yarn types, designs to patterns.This condition is worsened by the lack of forms of promotion carried out by songket craftsmen, so that it requires maximum effort, either through government policy or the company itself to work together to encourage promotional efforts to market the existing songket production, not only can it exist in the domestic market but also be able to exist in foreign market. with this, this paper will improve the quality of songket in South Sumatra.